واقع التمويل بالاعتماد الايجاري في الجزائر - بشير دهانة; وليد عريق; نسيم صالحي (جامعة الوادي University Of Eloued, 2024)
"يهدف هذا البحث إلى إبراز دور الاعتماد المستندي في تمويل التجارة الخارجية، وذلك بأخذ بدراسة ميدانية في البنك الخارجي الجزائري وكالة ولاية الوادي، ومن أجل بلوغ هذا الهدف تم الاعتماد على المنهج الوصفي في الفصل النظري، حيث تطرقنا لمقاربة نظرية للاعتماد المستندي والتجارة الخارجية، وكذلك تم الاعتماد على المنهج الاستقرائي ومنهج دراسة الحالة في دراسة حالة البنك محل الدراسة من خلال تحليل واستقراء المعلومات من نتائج المقابلات. تم التوصل إلى إن الاعتماد المستندي هو أهم وسيلة وأحسن طريقة للتعامل على مستوى التجارة الخارجية؛، وأنه في بنك الجزائر الخارجي المتعاملون يعتمدون على الاعتماد المستندي الغير قابل للإلغاء والمؤكد لأنه أكثر ضمانا للمتعاملين، وأن الاعتماد المستندي يعتبر أنجع تقنيات تمويل التجارة الخارجية والأكثر استعمالا في البنك الخارجي الجزائري " "This research aims to highlight the role of documentary credit in financing foreign trade, by taking a field study in the Algerian Foreign Bank, the Valley State Agency, and in order to achieve this goal, the descriptive approach was relied on in the theoretical chapter, where we touched on a theoretical approach to documentary credit and foreign trade, as well as relying on the inductive approach and the case study approach in the case study of the bank under study through analysis and extrapolation of information from the results of interviews. It was concluded that documentary credit is the most important and best way to deal at the level of foreign trade, and that in the Foreign Bank of Algeria, dealers rely on irrevocable and certain documentary credit because it is more secure for customers, and that documentary credit is considered the most effective foreign trade financing technique and the most used in the Algerian Foreign Bank. "
مذكرة ماستر
Keywords: اعتماد الايجاري; مؤجر; مستأجر; مورد; بنك البركة وكالة الوادي.; leasing; lessor; lessee; supplier; Al Baraka Bank Oued Agency.